A Biomicrofluidic Screening Platform for Dysfunctional Endothelium‐Targeted Nanoparticles and Therapeutics. Issue 1 (5th January 2022) - Bazban-Shotorbani, Salime; Gavins, Felicity; Kant, Krishna; Dufva, Martin; Kamaly, Nazila
Abstract : Biomicrofluidic Models Biomicrofluidic models allow nanoparticle‐cellular interactions to be studied under physiological flow conditions. Investigating nanoparticle biophysicochemical properties in models that resemble disease can provide valuable information about the nano‐bio interface. By screening nanoparticles dynamically against a developed dysfunctional‐endothelium‐on chip model, Nazila Kamaly and co‐workers show in article number 2100092 that nanoparticle size is a dominant factor beyond targeting ligands. Furthermore, tight junction disruption can be restored by the inflammation resolving mediator Annexin A1.